2021
DOI: 10.21037/tlcr-20-1027
|View full text |Cite
|
Sign up to set email alerts
|

Low-level expression of necroptosis factors indicates a poor prognosis of the squamous cell carcinoma subtype of non-small-cell lung cancer

Abstract: Background: The programmed cell death pathway necroptosis may synergize with the DNA damage response (DDR) in opposing tumor progression. While our basic mechanistic understanding of the necroptotic cell death advances rapidly, its prognostic implications have not been thoroughly examined in cancers.Methods: We included 394 patients with stage I non-small-cell lung cancer (NSCLC) who underwent surgical tumor resection between 1 January 1997 and 31 December 2011 and measured expression levels of nine proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, necroptosis helps to strengthen the immune ability of anticancer drugs 11 . Decreased expression of necroptosis factors has been found in NSCLC tissues and was associated with worse prognosis in NSCLC patients 12,13 . The activation of necroptosis pathway has been shown to remarkably increased the killing ability of lung cancer cell mediated by chemotherapy drugs or radiation 14–16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, necroptosis helps to strengthen the immune ability of anticancer drugs 11 . Decreased expression of necroptosis factors has been found in NSCLC tissues and was associated with worse prognosis in NSCLC patients 12,13 . The activation of necroptosis pathway has been shown to remarkably increased the killing ability of lung cancer cell mediated by chemotherapy drugs or radiation 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Decreased expression of necroptosis factors has been found in NSCLC tissues and was associated with worse prognosis in NSCLC patients. 12,13 The activation of necroptosis pathway has been shown to remarkably increased the killing ability of lung cancer cell mediated by chemotherapy drugs or radiation. [14][15][16] Collectively, necroptosis may become a novel approach in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that some necroptosis-related molecules were biomarkers for prognostic ( Gong et al, 2019 ; Lim et al, 2021 ). In order to select the most likely candidate prognostic necroptosis-related genes, we performed the LASSO algorithm to identify a set of 26 necroptosis-related genes ( Figures 6A–B ).…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative mode of programmed cell death, necroptosis overcomes apoptosis resistance and may trigger and amplify anti-tumor immunity in cancer therapy ( Gong et al, 2019 ). Further, necroptosis is not only an important cellular process that regulates the evolution of cancer, but is also closely associated with the prognosis of many tumors ( Lim et al, 2021 ; Xin et al, 2022 ). In HCC, necroptosis driver genes correlate with tumor-infiltrating lymphocyte density, with CD8 + T cells clustering in tumors with higher expression of necroptosis-related genes ( Nicolè et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%